Novel Trajectory Control System on Mobile Robot Using Visual Feedback - Mardiyanto, Ronny; Zaman, Muhammad Qomaruz (JAVA Journal of Electrical and Electronics Engineering, 2016)
IEDs (Improvised Explosive Device) are one of the main causes of injuries during a war. IEDs are also the most commonly used weapon by malefactors for it is cheap and easy to be crafted. This weapon may vary in color, shape, and size. They can be triggered remotely by radio signal, pressure, or even timer. The complexity of their system has made them be carefully treated. One of the most promising solutions to counter these explosives is using EOD (Explosive Ordnance Disposal) robots. These robots may pack so many features to counter measure the varying types of IEDs. The more feature the robot has, the more difficult how it would be controlled. Some researchers have tried to add intelligent or autonomous features to aid the operator. In this study is proposed an autonomous feature to the robot. The robot will approach autonomously to the target while maintaining its trajectory. The trajectory control is using proportional control method with visual feedback. The robot is panning its body with the camera attached to maintain its trajectory. The data shows that with this control system the robot respond to the input in only 12 seconds, and during the experiment, its highest error is 6.5o of panning degrees. The accuracy of the system is relative to the distance of the robot and the target. The maximum distance is up to 330 cm.